(x-8)2-28=0

Simple and best practice solution for (x-8)2-28=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-8)2-28=0 equation:


Simplifying
(x + -8) * 2 + -28 = 0

Reorder the terms:
(-8 + x) * 2 + -28 = 0

Reorder the terms for easier multiplication:
2(-8 + x) + -28 = 0
(-8 * 2 + x * 2) + -28 = 0
(-16 + 2x) + -28 = 0

Reorder the terms:
-16 + -28 + 2x = 0

Combine like terms: -16 + -28 = -44
-44 + 2x = 0

Solving
-44 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '44' to each side of the equation.
-44 + 44 + 2x = 0 + 44

Combine like terms: -44 + 44 = 0
0 + 2x = 0 + 44
2x = 0 + 44

Combine like terms: 0 + 44 = 44
2x = 44

Divide each side by '2'.
x = 22

Simplifying
x = 22

See similar equations:

| y^2-2y^1+y=8cosx | | 5x+4=36x-15 | | 7(t+2)= | | 3a+(a-1)= | | (2x^3-2xy+y^2)dx+2(xy-x^2-2y^3)dy=0 | | x^2+61=10x | | 5a+1=7a-5 | | X-3+4x=3(3x-9) | | y^2-10y^1+25y=0 | | -48(y+1)=8(4y-6)-240 | | -21+1=m-3 | | f(x)=x^2+3x+8 | | -23=x+7 | | f(x)=x^2+3+8 | | 9(a+3)+5= | | n=-11+33 | | 5b-6-10b-8= | | 5y=67 | | (9x+3)(7x+1)= | | -6(0.2x+0.3)-3.2=-0.2 | | h(t)=-16t^2+50t+1 | | 4q^8+9r^2= | | x^4-x^3-5x^2+3x+6=0 | | 11-2x=-4x+3 | | (6x+6)(3x^2+7x+8)= | | x^4-x^3-5x^2+3x=6 | | 2y^2+30xy-2y^2+4y-4x= | | 4x^3-15x^2+25x=0 | | 11=2g+6-5g | | 26=30-26a | | f(2)=2x-1 | | 2x+2.5=9.5 |

Equations solver categories